Clinical image-based procedures : translational research in medical imaging : 5th International Workshop, CLIP 2016, held in conjunction with MICCAI 2016, Athens, Greece, October 17, 2016, Proceedings /: translational research in medical imaging : 5th International Workshop, CLIP 2016, held in conjunction with MICCAI 2016, Athens, Greece, October 17, 2016, Proceedings. (2016) - Unknown
No abstract available